Legal Analysis of the Issuance of SHGB Over Maritime Areas in Tangerang from the Perspective of Indonesian Agrarian Law - Naomi Audri Klarisa Sitompul; Christian Imanuel Siboro (Recht Studiosum Law Review, 2025)
The issuance of 263 Building Use Rights Certificates (SHGB) on the sea barrier along the northern coast of Tangerang, Banten, spanning more than 30 km, has sparked controversy among the public. The issuance of these SHGBs has been confirmed by the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (ATR/BPN), Nusron Wahid. Positivistically, the presence of the SHGB is actually contrary to a number of regulations in Indonesia, including Law No. 5 of 1960 concerning Agrarian Principles, Law No. 27 of 2007 jo. Law No. 1 of 2014, Government Regulation No. 18 of 2021, Constitutional Court Decision No. 3/PUU-VIII/2010, as well as the principles in Article 33 paragraph (3) of the 1945 Constitution. Beyond the issue of legality, from a sociological and empirical standpoint, the presence of SHGBs on the sea barrier in Tangerang also has negative ecological and economic impacts. These SHGBs disrupt the marine ecosystem and hamper the livelihoods of local fishermen, as they obstruct access to fishing areas. Therefore, this paper aims to further analyze the legal basis for granting Building Use Rights (HGB) within Indonesia’s agrarian system, examine the legality of granting HGB on the sea barrier in Tangerang, and assess the socioeconomic and ecological impacts of these SHGBs through a case study approach focusing on Tangerang.